DIARE DAN ASUPAN ZAT GIZI (PROTEIN, VITAMIN A, ZINC, KALSIUM, BESI) TERHADAP KEJADIAN STUNTING PADA ANAK UMUR 2 – 5 TAHUN - Irza Nanda Ranti; Meildy Estevanus Pascoal; Mizzy Christania Wowor (POLTEKKES KEMENKES MANADO, 2020)
ABSTRACT Stunting is a chronic nutritional problem in the period of growth and development since the beginning of life or in the First 1000 Days of Life. This situation is presented with a height z-score by age (TB / U) less than -2 standard deviations (SD) based on growth standards according to WHO (WHO, 2010). Based on the latest Riskesdas data in 2013, the prevalence of stunting in Kotamobagu City was 38.1%. This study aims to determine the relationship of diarrhea and nutrient intake (Protein, Vitamin A, Zinc, Calcium, Iron) to the incidence of stunting in children under five. This type of observational analytic study with cross sectional design. The number of samples as many as 41 toddlers taken with nonprobability techniques with purposive sampling method. The results showed that 70.7% of children with stunting nutritional status and 29.3% of children with normal nutritional status. 70.7% of children have had diarrhea and 29.3% of children have never had diarrhea. The results showed no relationship between intake of Protein, Vitamin A, Iron on the incidence of stunting in children under five in the Gogagoman Community Health Center. As for Diarrhea, Zinc intake, and Calcium have a significant relationship to the incidence of Stunting in children under five in the Gogagoman Community Health Center. Conclusion, there is a relationship between diarrhea, zinc intake, and calcium intake on the incidence of stunting. While the intake of protein, vitamin a, and iron has no relationship with the incidence of stunting. Keywords: Stunting, Diarrhea, Protein, Vitamin A, Zinc, Calcium, Iron